Un plan paso a paso para integrar el conocimiento adquirido en la parcela digital y diplomados en los programas académicos. - Lizarazo, Miguel; Ramos, Gresia Dalal; Bonilla, Melissa; Munoz, Luis Armando; Jimenez, Daniel Ricardo (2024)
The digital transformation of the agricultural sector in Latin America has driven the adoption of innovative technologies, including IoT, artificial intelligence, and remote sensing. However, in Guatemala, small and medium-sized producers face challenges in accessing and applying these technological tools to their production systems.